Mood state indicators for adolescent athletes based on POMS multidimensional model - Andrade, Elena; Arce, Constantino; Armental, Juancho; Rodríguez, Mauro; de Francisco, Cristina (Psicothema, 2008)
In this paper, we offer a short version of the POMS, with only 33 items, designed to apply to young Spanish athletes. One hundred and six male soccer players, aged 14 and 15 years, participated in the study. In order to select the proposed items, we tried to maximize three criteria: (1) items should be understood by subjects, (2) items should be perceived as conceptually similar as possible to the meaning of their respective factors, and (3) every factor should contain at least 4 items. To meet the second criterion, PROXSCAL scaling procedure was used, which allowed retaining the items closest to the meaning of each factor. All goodness-of-fit indexes were satisfactory in all the proximity analyses performed. In the proposed POMS version, the 33 items refer to seven mood factors, as follows: Tension (4 items), Depression (9 items), Anger (4 items), Vigour (4 items), Fatigue (4 items), Confusion (4 items), and Friendliness (4 items).